Effect of Inulin Fortified Diet on the Growth, Carcass Composition, Haematological Responses, Intestinal Microbiota and Histological Alterations of GIFT - Joshna, M.; Manimaran, H. (International Journal of Bio-resource and Stress Management, 2024)
The experiment was conducted in the year 2021 at wet laboratory, Advanced Research Farm Facility, Dr. M.G.R. Fisheries College and Research Institute, TNJFU, Madhavaram, Tamil Nadu, India to investigate the effect of inulin on the growth performance, haematology, carcass composition, intestinal microbiota and histology alterations of Genetically Improved Farmed Tilapia (GIFT). Four experimental diets were designed to incorporated inulin at 0 (basal diet), 0.5 g kg-1, 1.0 g kg-1 and 1.5 g kg-1. Fish with an initial mean weight of 0.85±0.02 g were allotted 12 tanks of 50 L capacity at a density of 20 fish per tank and fed with 5% of their body weight, two times a day. At the end of the experiment, the growth performance, feed utilization and haematology parameters were improved in fish fed with inulin at 1.5 g kg-1 of diet compared to control and other dietary treatments. A diet with 1.5 g kg-1 of inulin improved the total bacteria and lactic acid bacteria in the intestine of GIFT. The addition of inulin altered the intestine and liver histology. In the intestine, villi are short and dilated in fish fed with inulin on the 60th day, whereas hepatocytes and sinusoids showed vacuolation and congestion in the liver in fish fed with inulin on the 30th and 60th day. No histological change was observed in the gill. Substantially dietary inulin at 1.5 g kg-1 had beneficial effects on the growth performance, haematology and intestinal microbiota of GIFT.